A Comparison of the Effectiveness of Serratus Anterior Block Vs Intercostal Block as Analgesia for the Management of Post-Thoracotomy Pain - Naseer, Hira; Mateen, Abdul; Fatima, Nimra; Naqvi, Syed Muhammad Raza; Mumtaz, Aisha (Biological and Clinical Sciences Research Journal, 2025)
Post-thoracotomy pain is a significant clinical challenge that can affect patient recovery and increase the risk of chronic pain. Regional nerve blocks such as intercostal nerve block (ICNB) and serratus anterior plane block (SAPB) are increasingly utilized for postoperative analgesia in thoracic surgery, yet comparative data on their safety and efficacy remain limited. Objective: To compare the effectiveness and safety of intercostal nerve block and serratus anterior plane block for the management of post-thoracotomy pain. Methods: This prospective study was conducted in the Thoracic Surgery Department of Mayo Hospital, Lahore, from February 2024 to February 2025. A total of 100 patients undergoing thoracotomy with an ASA physical status I or II were included. Patients were consecutively assigned to two groups: Group A (n=50) received intercostal nerve block, and Group B (n=50) received serratus anterior plane block. The primary outcome was the assessment of pain intensity using the Visual Analogue Scale (VAS) at rest and during coughing up to 48 hours postoperatively and at 3 months post-surgery. Secondary outcomes included analgesic requirements and identification of predictors for chronic postoperative pain. Statistical analysis was performed using SPSS version 25. Independent t-tests and chi-square tests were applied, and a p-value <0.05 was considered statistically significant. Results: Group B demonstrated significantly lower VAS scores at 48 hours at rest (p=0.001) and at 24 hours during coughing (p<0.001) compared to Group A, although VAS at rest was higher at 6 hours postoperatively in Group B (p=0.020). Group A required significantly higher doses of nalbuphine (p<0.001), ketorolac (p=0.006), and flurbiprofen (p=0.004). No adverse effects related to nerve blocks were reported in either group. Risk factors significantly associated with chronic postoperative pain included VAS at rest at 12 hours (p=0.049), surgical duration (p=0.050), and chest tube duration (p=0.032). Conclusion: Both intercostal nerve block and serratus anterior plane block are safe and effective for managing post-thoracotomy pain. However, SAPB may offer superior analgesia in the immediate postoperative period. Pain intensity at 12 hours postoperatively, surgical duration, and chest tube duration are significant predictors of chronic postoperative pain.